Variability of Kappaphycus alvarezii cultivation in South-Sulawesi (Indonesia) related to the monsoon shift: Water quality, growth and colour quantification - Laurent Barillé; Iona L.R. Paterson; Simon Oiry; Agus Aris; Elizabeth J. Cook-Cottier; Nurjannah Nurdin (Aquaculture Reports)
Kappaphycus alvarezii is a red eucheumatoid seaweed of high global economic significance due to its carrageenan content. Nevertheless, notable unexplained fluctuations in growth and production persist, exacerbated by limited data availability, while spatial and temporal factors remain unclear. This research aimed to characterise the variability of water quality, growth and thallus colouration of a green morphotype of K. alvarezii related to the monsoon shift in South Sulawesi, Indonesia. The experiment was conducted from July to November over contrasting dry and wet seasons. Three cultivation cycles of ca. 40 days were monitored: Cycle 1 (July/August), Cycle 2 (August/October), and Cycle 3 (October/November). The Southeast monsoon season (Cycles 1 and 2) was characterised by higher salinities, but lower temperatures and nutrients. During the wet Northwest monsoon season (Cycle 3), the water was hotter, with higher concentrations of nitrates and phosphates, but lower salinities. The highest growth rate at harvest of 5.0 %.day−1 was observed during Cycle 3. Fresh biomass production per m of the cultivation line was significantly higher for Cycle 3, 827.78 ± SD 101.50 g.m−1 compared to Cycle 1 and 2, respectively 484.38 ± SD 11.27 g.m−1 and 510 ± SD 25.69 g.m−1. The higher growth during the West monsoon was likely due to the increase in nutrient concentrations brought by freshwater runoff, which coincided with higher rainfall. The spectral signature of the green morphotype was very similar to green macrophyte spectra with higher reflectance in the 500–600 m wavelength region. A decrease in the greenness optical index at 550 nm was observed at the end of each cultivation cycle, with the thalli appearing darker. This study showed marked variations in growth rates, with significantly higher growth during the wet West monsoon, in conjunction with a higher risk of production loss due to the prevalence of ice-ice disease.